The Role of Occupational Therapy in People with Mental Health - M. Anghel; L.D. Botoc (Editura Universitatii Transilvania din Brasov, 2023)
Unfortunately, in our country, in some situations, the level of occupational therapy activities is limited to the precarious material conditions in different types of institutions. Despite the current improvements, there is still an acute need for adequate spaces and materials to carry out quality occupational therapy activities. The presence of these negative aspects, which is added to the lack of qualified personnel in the field, diminishes the quality of the recovery process in the institutions. The scientific challenge that is the subject of this paper is to highlight the role of occupational therapy in the exploration of specific resources for institutionalized persons, necessary for the development of autonomy. The objective of the research is to implement an intervention program, through remedial activities, that will contribute to direct involvement in daily life for people with mental health problems. The main conclusion of the research is that by applying remedial activities adapted to the specific needs of the client, the components of occupational performance can be improved, by increasing the degree of involvement in daily activities for institutionalized people.